2001
DOI: 10.1046/j.1365-2605.2001.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Circannual variation in human semen parameters

Abstract: The aim of the present study was to determine whether there were significant monthly variations in the semen parameters (i.e. volume, sperm count, total sperm count, motile and normal sperm count) of men living in a Mediterranean climate area. A total of 10 877 semen analysis results were included. Semen samples were obtained as a part of an initial screening of male partners from couples with infertility problems who were attending our laboratory from 1970 to 2000. Log transformation and cubic root transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
5
17
0
3
Order By: Relevance
“…Seasonal changes in semen quality have been reported in several locations (Gyllenborg et al, 1999;Andaloz et al, 2001;Chen et al, 2003Chen et al, , 2004Mallidis et al, 1991). In our study, during spring, when higher OP urinary levels were registered, lower levels of sperm concentration and sperm count were recorded.…”
Section: Semen Parameterssupporting
confidence: 50%
“…Seasonal changes in semen quality have been reported in several locations (Gyllenborg et al, 1999;Andaloz et al, 2001;Chen et al, 2003Chen et al, , 2004Mallidis et al, 1991). In our study, during spring, when higher OP urinary levels were registered, lower levels of sperm concentration and sperm count were recorded.…”
Section: Semen Parameterssupporting
confidence: 50%
“…In humans, the effect of season rotation on sperm parameters is still controversial. Several studies confirmed a seasonal pattern of sperm variations (Andolz et al, 2001;Chen et al, 2004), whereas others did not (Menge and Beitner, 1989;Ombelet et al, 1996). The finding of seasonal change of chromatin condensation in human sperms seems to confirm this hypothesis (Henkel et al, 2001;Snyder, 1990).…”
Section: Discussionmentioning
confidence: 86%
“…With regard to sperm concentration and sperm motility and vitality, contradictory results have been published. While Mortimer et al (1983) and Ombelet et al (1996) could not find significant seasonal variations of these parameters, others clearly emphasize such an effect (Tjoa et al, 1982;Politoff et al, 1989;Saint Pol et al, 1989;Centola and Eberly, 1999;Andolz et al, 2001;Henkel et al, 2001). Seasonal variations in sperm concentration were clearly not attributable to differences in sexual abstinence (Gyllenborg et al, 1999).…”
Section: Discussionmentioning
confidence: 98%